PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN UNIT SHARED SERVICE PT. TELKOM AKSES AREA RIAU DARATAN - Devianalita Agnus; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the effect of work motivation and career development on the performance of PT. Telkom Access Riau Riau Area. Employee performance is the work of individuals in an organization. The achievement of organizational goals cannot be separated from the resources owned by organizations that are driven or run by employees who play an active role as actors in efforts to achieve the goals of the organization. To improve the performance of company employees must pay attention to supporting factors that will affect the performance. This research was conducted at the office of PT. Telkom Access Riau Riau Area, located on Jl. Cempedak No. 8 Wonorejo Kec. Marpoyan Damai, Pekanbaru City. The sample of this research was taken as many as 37 by the census method. In this research the method used is descriptive and quantitative. Data obtained from interviews, documents in the company and subsequent questionnaires were obtained and then tested with statistics through the SPSS program. From the analysis of the data include validity, reliability, simple linear regression, multiple linear regression tests. In the test results that work motivation has a positive and significant effect on employee performance, career development has a positive and significant effect on employee performance then work motivation and career development have a positive and significant effect on employee performance in employees of PT. Telkom Access Riau Riau Area.Keywords: Work Motivation, Career Development, Employee Performance